The Impact Of Green Supply Chain Management On Environmental and Economic Performance In The Ceramic Industry: A Case Study of PT. Muliakeramik Indahraya - Sutrisna, Raafi Jaya; Azis, Anton Mulyono (The Es Economics and Entrepreneurship, 2025)
The ceramic industry plays a crucial role in Indonesia's economy, particularly in supporting the continuously growing property and infrastructure sectors. However, the significant contribution of this industry is not without environmental issues, especially concerning carbon emissions from the firing process, production waste, and high natural resource consumption. As stakeholder pressure and global demands for sustainable business practices increase, companies are required to adopt strategies that not only enhance operational efficiency but also minimize negative environmental impacts. Therefore, the implementation of Green Supply Chain Management (GSCM) becomes essential in reducing environmental harm and improving operational efficiency. This study aims to analyze the influence of GSCM on environmental and economic performance in the ceramic industry, using PT. Mulia Keramik Indahraya as a case study. The research employs a quantitative approach with an associative-causal method. Data was collected through questionnaires distributed to 72 employees and analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The results indicate that Stakeholder Pressure has a significant effect on Green Supply Chain Management (p-value 0.000 < 0.05), demonstrating that stakeholder pressure drives GSCM implementation. Green Supply Chain Management also significantly influences Economic Performance (p-value 0.000 < 0.05), meaning that GSCM adoption enhances the company's economic performance. However, the effect of Green Supply Chain Management on Environmental Performance is not significant (p-value 0.064 > 0.05), suggesting that GSCM implementation has not yet had a measurable impact on environmental performance. Meanwhile, Environmental Performance significantly affects Economic Performance (p-value 0.001 < 0.05), indicating that improved environmental performance also boosts the company's economic performance.